2018
DOI: 10.2215/cjn.10150917
|View full text |Cite
|
Sign up to set email alerts
|

Dementia, Alzheimer’s Disease, and Mortality after Hemodialysis Initiation

Abstract: Background and objectives Older patients with ESKD experience rapid declines in executive function after initiating hemodialysis; these impairments might lead to high rates of dementia and Alzheimer's disease in this population. We estimated incidence, risk factors, and sequelae of diagnosis with dementia and Alzheimer's disease among older patients with ESKD initiating hemodialysis.Design, setting, participants, & measurements We studied 356,668 older (age $66 years old) patients on hemodialysis (January 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 50 publications
3
61
0
2
Order By: Relevance
“…This review showed that cognitive impairment in older haemodialysis patients is positively correlated to mortality. Older haemodialysis patients are also at potential risk of being befalled with Alzheimer's disease, and receiving this diagnose is associated with an increased mortality [46,47]. Another study found that dementia was associated with an increased risk of death and dialysis drop out in adults aged over 75 years on dialysis [31].…”
Section: Discussionmentioning
confidence: 99%
“…This review showed that cognitive impairment in older haemodialysis patients is positively correlated to mortality. Older haemodialysis patients are also at potential risk of being befalled with Alzheimer's disease, and receiving this diagnose is associated with an increased mortality [46,47]. Another study found that dementia was associated with an increased risk of death and dialysis drop out in adults aged over 75 years on dialysis [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that frailty is a key predictor of adverse events while on dialysis [12, 37], on the waitlist [19, 20], or during/after KT [19, 26, 38]. Consequently, clinical applications of frailty assessments have emerged, such as for improving screening.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, impairments in executive function in patients with ESKD may suggest early signs of dementia, particularly vascular dementia, and in many cases, Alzheimer's disease . In a national study of 356 668 older patients initiating HD, the 5‐year risk of diagnosed dementia accounting for the competing risk of death and HD withdrawal was 16% for women and 13% for men; the corresponding Alzheimer's disease diagnosis risks were 2.6% for women and 2.0% for men . These older HD patients with a dementia diagnosis were at a 2‐fold higher risk of subsequent mortality, as were those with a diagnosis of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%